The oracle study – fibromyalgia, prevalence and severity in the hospital setting - Mohammad Ali Arif; Fibhaa Syed; Rauf Niazi; Saba Ali Arif; Umme e Laila Hashmi; Zakir Shah (Journal of the Pakistan Medical Association, 2021)
Objective: The aim of the present study was to assess the prevalence and severity of Fibromyalgia in hospital visiting patients. Methods: A total of 750 patients aged 18 to 75 years were enrolled at the Pakistan Institute of Medical Sciences, Islamabad from July 2018 – January 2019. Demographic data, the presence of comorbidities and previous medication, were recorded for each patient and the 2010/2011 modified ACR (American College of Rheumatology) preliminary diagnostic criteria for fibromyalgia was applied. If fibromyalgia was diagnosed, the FIQR (Fibromyalgia impact questionnaire) was administered to assess the severity of FM. Results: The prevalence of fibromyalgia in hospital visiting patients was found to be 33.3% (n=250), with a female preponderance of 76% (n=190) in the diagnosed subset. Females were more than twice as likely to have fibromyalgia as their age matched male counterparts (OR 2.87, 95% CI 2.05 – 4.04, p<0.0001). The presence of diabetes, anxiety and rheumatoid arthritis but not other comorbidities (p<0.0001), advancing age (p=0.002) and increased BMI (p=0.004) were found to be significantly associated with FM. In patients diagnosed with FM, over 70% (n=180) had been previously diagnosed as having musculoskeletal pain with 66% (n=165) being on long term NSAID therapy. Multiple regression analysis showed FM severity was not influenced by comorbidities, marital status, education or economic status. A unique finding was a later age of menarche (R2=0.194, p=0.009) and menstrual irregularity (R2=0.229, p=0.003) being associated with more severe fibromyalgia symptoms. Continuous....